2015
DOI: 10.1111/pde.12459
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Hamartoma of Infancy: A Firm Plaque Presenting with Hypertrichosis and Hyperhidrosis

Abstract: Fibrous hamartoma of infancy (FHI) is a rare, benign, soft tissue tumor. The lesion's clinical resemblance to more aggressive soft tissue tumors of childhood makes histologic diagnosis paramount. We report a unique presentation of a FHI associated with localized hypertrichosis and hyperhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…First, Weinberger et al 7 reported a case of FHI presenting as a perspiring neck mass in 1993. Next, in 2015, Melnick et al 6 reported a case of FHI presenting with hypertrichosis and hyperhidrosis, which is quite similar to our case. Both cases were reported in the US, and no case of FHI presenting with hyperhidrosis has been reported in Korea, until now.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, Weinberger et al 7 reported a case of FHI presenting as a perspiring neck mass in 1993. Next, in 2015, Melnick et al 6 reported a case of FHI presenting with hypertrichosis and hyperhidrosis, which is quite similar to our case. Both cases were reported in the US, and no case of FHI presenting with hyperhidrosis has been reported in Korea, until now.…”
Section: Discussionsupporting
confidence: 88%
“…However, a review of the literature reveals only 2 cases of FHI presenting with hyperhidrosis in the world, and no case in Korea. 6 7 In this study, we report the first Korean case of FHI with hyperhidrosis and hypertrichosis.…”
Section: Introductionmentioning
confidence: 93%
“…Its pathogenesis and biological characteristics are still unclear. The disease usually occurs in children less than two years of age, of which approximately 23% are born with it, and male to female incidence ratio is approximately 2.4[ 5 ]. FHI mostly occurs in the axilla, followed by the upper arm, thigh, back, groin, buttocks, and external genitalia[ 4 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…244,245 The overlying skin is usually unremarkable with a few reported exceptions. 246,247 In a minority of cases, the tumor may be noted at birth. Most tumors measure less than 5 cm with the exceptional case greater than 10 cm.…”
Section: Fibrous and Myofibroblastic Tumorsmentioning
confidence: 99%